2019
DOI: 10.4314/ijs.v21i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of metallo-b-lactamase producing gram-negative bacteria in a hospital with no history of Carbapenem usage in northwest Nigeria

Abstract: Carbapenems are among the antibiotics of last resort against infections caused by antibiotic resistant bacteria. However, resistance to this important class of antibiotic is on the increase due to expression of metallo-betalactamases (MBLs). This study investigated the occurrence of MBL-producing bacteria in a healthcare facility in Sokoto, Nigeria. Swabs were collected from the rectum (n = 29) and bed linens (n = 27) of patients within the surgical wards of the hospital between March and August, 2018 and proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Previous reports across the country have established varying rates. For example, 28% carbapenem resistance was reported in the preceding year in one of the hospitals among carbapenem-naive patients [ 18 ]. Also, in a neighbouring West Africa country, Ghana, a rate of 66% carbapenem-resistant Gram-negative bacteria has been reported [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports across the country have established varying rates. For example, 28% carbapenem resistance was reported in the preceding year in one of the hospitals among carbapenem-naive patients [ 18 ]. Also, in a neighbouring West Africa country, Ghana, a rate of 66% carbapenem-resistant Gram-negative bacteria has been reported [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interest in research on carbapenem resistance began recently. Most studies on CPE have been limited to phenotypic testing [ 17 , 18 ]. However, a few studies have used genotypic methods to establish the occurrence of carbapenemase genes among clinical and non-clinical bacterial isolates in Nigeria [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the occurrence of mcr-mediated colistin resistance among 99 colistin resistant isolates; Escherichia coli (67/99), Klebsiella pneumoniae (30/99), Citrobacter werkmanii (1/99), and Alcaligenes faecalis (1/99) from humans and animals in Nigeria (Ngbede et al, 2020). Studies have also reported a high prevalence, up to 52%, of carbapenem resistance mediated by carbapenemase producing genes in samples from humans in Nigeria (Ogbolu and Webber, 2014;Jesumirhewe et al, 2017;Olowo-okere et al, 2019;Otokunefor et al, 2019;Ogbolu et al, 2020;Olalekan et al, 2020;Olowo-Okere et al, 2020;Shettima et al, 2020). These findings suggest that resistance to the last resort drugs carbapenem and colistin is a significant problem in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…11 Despite the untenable rate of antibiotic resistant bacterial infections reported in most Nigerian cities, there is substantial gap in the surveillance of these infections in several Nigerian cities especially in northwest Nigeria where limited research has been done on the prevalence of difficult to treat infections. 12,13 In the few studies conducted, a limited number of antimicrobial classes have been tested. This study therefore aimed to comprehensively investigate the prevalence of multidrug resistant (MDR) Gram-negative bacterial infections among patients attending two major hospitals in northwest Nigeria.…”
Section: Introductionmentioning
confidence: 99%